The shadow throne - Nielsen, Jennifer A. (Nielsen, Jennifer A. Ascendance series ;, 2014)
Young King Jaron has had nothing but trouble with his advisors and regents since he ascended the throne of Carthya, and now King Vargan of Avenia has invaded the land and captured Imogen--and Jaron must find some way to rescue her and save his kingdom.